Efficiency of Vehicle Operation - Belyaev, Alexander Ivanovich; Afanasyev, Alexander Sergeevich (International Journal of Economics and Financial Issues, 2016)
The paper presents the results of researching the mileage of vehicle efficient operation (MVEO) based on the method of using the techno-economic criterion (TEC). As a result of our work, we have defined and substantiated the MVEO for motor vehicles operated in the conditions of St. Petersburg and the Leningrad region, and calculated the lifetime of motor vehicles with the use of the techno-economic criterion. In defining MVEO and in the use of the techno-economic criterion an important role was played by complexity of running repair (RR) of the rolling stock not regulated by the manufacturers of vehicles of these brands. It has been found that the value of MVEO is influenced by a number of various factors, for example: efficiency of the production-technical base, qualification of the personnel, operating conditions (road, transport, etc.), and the level of instrumentation. Each of them has its specific weight in the MVEO value, but using the work load of RR parameter is explained by its complexity, and all these factors influence its value in varying degree. Keywords: mileage of vehicle efficient operation; techno-economic criterion; vehicle efficient operation. JEL Classifications: L62, L91, R49.